2020
DOI: 10.1111/vde.12825
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous mural folliculitis in a dog treated with ciclosporin and methotrexate

Abstract: Background Canine granulomatous mural folliculitis is a very rare cause of scarring alopecia with unknown pathogenesis. Hypothesis/objectives To report a case of granulomatous mural folliculitis in a dog treated with ciclosporin (Cs) and methotrexate (MTX). Animal A 13‐year‐old spayed female Pyrenean shepherd dog with a one month history of scarring alopecia. Methods and results Histopathological examination revealed a granulomatous and lymphocytic mural and necrotizing folliculitis and furunculosis. Immunoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…1,3 In the case described by Declercq and Vercauteren, an underlying drug reaction to amoxicillin clavulanate and/or tolfenamine acid was suspected. 4 However, no drugs or vaccine triggers were implicated by Panzuti et al 5 For the case described herein, onset of lesions was reported to occur several months prior to initiation of therapies, thus no drug or vaccine triggers were suspected.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…1,3 In the case described by Declercq and Vercauteren, an underlying drug reaction to amoxicillin clavulanate and/or tolfenamine acid was suspected. 4 However, no drugs or vaccine triggers were implicated by Panzuti et al 5 For the case described herein, onset of lesions was reported to occur several months prior to initiation of therapies, thus no drug or vaccine triggers were suspected.…”
Section: Discussionmentioning
confidence: 79%
“…once daily) and subcutaneous methotrexate injections (0.25 mg/kg once weekly for 2 weeks, then 0.5 mg/kg once weekly thereafter) given for 4 months, followed by discontinuation of ciclosporin and maintenance with weekly methotrexate injections at 0.5 mg/kg for an additional 8 months until the dog was lost to follow up. 5 Pruritus and skin lesions resolved for this dog, and some hair regrowth occurred, though cicatricial alopecia remained on parts of the face, abdomen, and legs. Granulomatous mural folliculitis is often reported to be associated with an adverse drug reaction, though the wide range reported in clinical and histopathologic severity could suggest a more varied eitiology.…”
Section: Discussionmentioning
confidence: 81%
“…Activation of virus and prehistoric activation protein in viruses, can still activate protein activation system and bacterial immunity in problems, still virus and pre-problem immunity protein in inflammatory family problems). The disease is locally, but with low metastatic potential, there is an early diagnosis, it has a good prognosis, however, it can occur [8]. In cats, they mainly serve the ears and nasal region, while in dogs they mainly serve the digits and eyelids.…”
Section: Introductionmentioning
confidence: 99%
“…3 Idiopathic GMF has also been recently described in a canine case report, in which stabilization of skin lesions was achieved with combination immunosuppressive therapy. 31 Equine linear alopecia is another idiopathic entity with GMF, clinically characterized by circular areas of alopecia arranged in a linear, vertically-oriented configuration on the neck, shoulders, and/or lateral thorax. 40…”
mentioning
confidence: 99%
“…3 Idiopathic GMF has also been recently described in a canine case report, in which stabilization of skin lesions was achieved with combination immunosuppressive therapy. 31 Equine linear alopecia is another idiopathic entity with GMF, clinically characterized by circular areas of alopecia arranged in a linear, vertically-oriented configuration on the neck, shoulders, and/or lateral thorax. 40 Domestic goats have many different skin diseases with overlapping gross lesions; however, the known differential diagnoses for caprine GMF are limited to OvHV-2 infection and dermatophytosis.…”
mentioning
confidence: 99%